2015
DOI: 10.1039/c5ta02674a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nitrogen-doped graphite felts as positive electrodes using polypyrrole as a coating agent in vanadium redox flow batteries

Abstract: A novel method for preparing nitrogen-doped graphite felts as positive electrodes in vanadium redox flow batteries was developed and studied. These materials were synthesized by directly coating a thin polypyrrole layer on the graphite felt surface followed by subsequent carbonization in the presence of Co (NGF-Co).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 40 publications
(44 reference statements)
1
48
1
Order By: Relevance
“…11 Therefore, selecting suitable electrode materials is crucial in VRFB design. 5 Carbonaceous materials such as carbon paper, graphite felt, carbon cloth, and graphite powder have been investigated as electrode materials for VRFBs. 12,13 Among them, graphite felts (GFs) are the most widely used because of their porous threedimensional network structure; low cost; high electrical conductivity, chemical and mechanical stability, and specific surface area; resistance of corrosion in acidic solutions, and a wide operating potential range.…”
mentioning
confidence: 99%
“…11 Therefore, selecting suitable electrode materials is crucial in VRFB design. 5 Carbonaceous materials such as carbon paper, graphite felt, carbon cloth, and graphite powder have been investigated as electrode materials for VRFBs. 12,13 Among them, graphite felts (GFs) are the most widely used because of their porous threedimensional network structure; low cost; high electrical conductivity, chemical and mechanical stability, and specific surface area; resistance of corrosion in acidic solutions, and a wide operating potential range.…”
mentioning
confidence: 99%
“…Recently, nitrogen‐doped carbon materials have been investigated as electrode materials for VRFBs because doped nitrogen atoms in carbon materials can act as effective electrocatalysts for the electrochemical reaction of vanadium ion redox couples . By improving the charge transfer kinetics for redox reactions of vanadium ions, Park et al .…”
Section: Introductionmentioning
confidence: 99%
“…Park et al . reported that cobalt impregnated nitrogen‐doped graphite felt using in situ polymerization of polypyrrole exhibited fast electrochemical kinetics of vanadium redox reactions . Shao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While not involved in direct energy storage, electrode materials play a crucial role in the overall power density and energy efficiency as the electrodes must provide sites for reactions and efficiently transport charge to and from the active species [13]. Thus, potential VRFB electrode materials must have high electrical conductivity, mechanical strength, large specific surface area, good stability in (acidic) electrolytes, and electrochemical activity [14].…”
Section: Introductionmentioning
confidence: 99%